A study of brainstem auditory evoked responses in normal human subjects and normal variations as a function of stimulus and subject characteristics - Ray, Bidhan; Raman, Santosh; Sen, Sukanta; Sharma, Manuprita; Ghosh, K. C.; Saha, A. M. (International Journal of Research in Medical Sciences, 2016)
Background: Brainstem auditory evoked responses (BAERs) are electrophysiological investigations have widespread clinical utility in neurology, audiology, neonatology and anesthesiology. BAER responses exhibit a normal variability due to various non-pathologic factors and age is one of the variables suggested to have considerable influence on normal BAE responses. Aging changes in the auditory system may significantly influence the interpretation of the auditory brainstem responses in comparison with younger adults. The present study was undertaken to study the different parameters of brainstem evoked responses in normal subjects and their variations with changing stimulus and subject characteristics among average Indian people. Methods: The test was conducted on 50 neuro-audiologically normal subjects (age-group of 5-60 years) selected from the OPD of ENT Department. Various audio-vestibular tests they were subjected to brainstem evoked response audiometry and responses were studied regarding various parameters of ABR details. An attempt was made to find out a normal range, normative values of various parameters and their variations with respect of their stimulus intensity and subject characteristics. Results: In the present study it was observed that absolute latencies of all waves decreased with increasing stimulus intensity. The mean absolute latency values of all waves were prolonged in male than those of female subjects. The mean inter-peak latency values of I-III, III-V and I-V were also prolonged in male. Effects of change in stimulus rate on absolute latencies of all waves were observed. There were increases in absolute latencies of all waves with increasing stimulus rate. Conclusions: Increased stimulus intensity caused decrease in latency values of all values. Wave V showed lesser degree of variation than the other components. Increase in stimulus rate caused increase in latency of all waves. Wave V showed lesser degree of variation than the other components. BERA can be performed with a wide range of stimulus variations. But what was clear in conclusion was that 60dB SL was the suitable intensity level. Also a wide variety of stimulus rate can be used in combination with either of the stimulus polarity. So any combination of stimulus intensity, rate and polarity may be used for clinical application of BERA. But essence is that there should be a prior adjustment of parameter norms according to subject and stimulus characteristics.